2004
DOI: 10.2516/ogst:2004040
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Ethanol As a Fuel for Dedicated Engine

Abstract: Résumé -Potentiel de l'éthanol en tant que carburant pour un moteur dédié -Un des défis majeurs de l'industrie automobile est de réduire les émissions de gaz à effet de serre et, en particulier, celles du CO 2 . Plusieurs programmes de recherche sont en cours sur ce sujet, visant la réduction de la consommation des véhicules, mais aussi l'optimisation de la composition des carburants. Il est en effet essentiel de prendre en compte l'ensemble du processus, de la production des carburants aux émissions des véhic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 5 publications
4
63
0
7
Order By: Relevance
“…Research into the quality of fuels and their biocomponents also presented by another researchers, for example: Baltėnas et al (1998); Pukalskas (2002); Jeuland et al (2004); Li et al (2005); Makarevičienė et al (2005) …”
Section: Introductionmentioning
confidence: 94%
“…Research into the quality of fuels and their biocomponents also presented by another researchers, for example: Baltėnas et al (1998); Pukalskas (2002); Jeuland et al (2004); Li et al (2005); Makarevičienė et al (2005) …”
Section: Introductionmentioning
confidence: 94%
“…For the comparison of emissions, CO emissions resulting from the use of hydrous ethanol was less than that of gasohol by 41%, the reason behind its water present during combustion might act to decrease CO emissions by way of the water-gas shift mechanism, it also found that the HC produced from the use of hydrous ethanol was higher than that of gasohol by 56%. Trends in HC emissions are highly variable since it depends on charge heterogeneity [83], combustion chamber design [10], flame quenching [84] and other engine related parameters. However, hydrocarbon emissions would increase when the mixtures were down beyond the lean limit [74].…”
Section: Regulated Emissions (Co Co 2 No X Hc and Pm)mentioning
confidence: 99%
“…O potencial do etanol como combustível dedicado foi avaliado em um pequeno motor turbo de ignição por centelha por Jeuland et al [13]. Vantagens e desvantagens do etanol são listadas no seu trabalho.…”
Section: Introductionunclassified
“…Este aumento, por sua vez, aumenta a probabilidade de ocorrência de detonação. Assim, misturas com maior número de octanas são desejáveis, uma vez que permitem a operação em tais condições [4,5,13,16,17].…”
Section: Introductionunclassified